Designing Integrated Health Monitoring Systems Using Sensors, IoT, and Informatics Tools - Dr Anupama P.Patil (The Bioscan, 2025)
New digital health technologies have changed and improved the ways healthcare services are given, overseen and handled. In this paper, we describe a method for designing integrated health monitoring systems using sensors, IoT and health informatics tools. Its objective is to make it easier for people to monitor their health, find diseases early on and receive timely help, mainly for chronic diseases and care of the elderly. We show how these technologies are structured, built and linked and we assess the outcomes of using them in simulation and deployment tests. Results from our research indicate that these platforms offer improved accuracy of data, more active patient involvement and higher healthcare efficiency. With an integrated system, healthcare can provide instant, customized and remote support to patients.